Exploration of Financial Management Models for Fisherman Groups in Soro Village, Dompu District (Comparation Study of Successful Fishermen and Unsuccessful Fishermen) - Larasati, Fani; Suryantara, Adhitya Batu (Formosa Journal of Science and Technology, 2024)
This study aims to explore financial management practices within fishing groups by comparing successful and unsuccessful groups. The research method employed is a qualitative approach with a comparative case study. Data were collected through in-depth interviews and direct field observations. The results show that successful fishermen have comprehensive financial planning, multiple income sources, saving and investing habits, good debt management, and an adequate level of financial education. In contrast, unsuccessful fishermen tend to lack clear financial planning, rely on fish catches as their sole income source, have little or no savings and investments, have poor debt management, and lack financial education.